Detection and track prediction of tropical cyclones in the bay of bengal using a regional climate model - Wijemannage, Ajith Lasantha Kumara
A Regional Climate Model (RegCM3, version 3.1) is used in detecting and predicting the tracks of four tropical cyclones (TC) that formed in the Bay of Bengal during the period October-December, 2000. the sensitivity of model outputs to two sets of applied initial and boundary conditions, namely ECMWF/ERA-40 and NCEP-NCAR/NNRP2 reanalysis data sets, are also assessed.